KAJIAN TEKNIS DAN EKONOMIS ENERGI SOLAR CELL SEBAGAI TENAGA ALTERNATIF LAMPU CELUP PENGUMPUL IKAN PADA KAPAL MINI PURSE SEINE - Fenas Aditya Firdaus; Ari Wibawa Budi Santoso; Berlian Arswendo A A (Jurnal Teknik Perkapalan, 2013)
Problems in fuel prices started to rise and a rare requires innovation in resource development alternative and environmentally friendly that will not be depleted if used. Source of energy that has not realize is solar energy. The sun provides energy to about 100,000 terawatt to earth about 10,000 times more than the energy consumed on earth at this time. Generally the operation of purse seine using light attractor in the sea with a power of 15000-35000 watts, even fishermen tend to magnify up to 80,000 watts. It is must be considered because there will be social conflict between fishermen and also less effective use of light resulting in energy waste. In conducting this research, some planning stages of battery capacity and solar panels. And also the design of the model dipped lamp buoys collecting fish (Ampala) on a mini purse seine vessels. In planning of the placement of solar panels available solar panel type polycrystalline needs 1 unit (50 wp) and battery lithium 4 units (@ 6 Ah) for 4 units ampala on mini purse seine vessel. While the long time charge from the solar panel to the battery in 4 units in cloudy weather is 6 hours 24 minutes. In terms of economic ampala new models every year comparative results obtained are cheaper than ampala fishermen. By comparison Ampala fishermen: Ampala latest models = Rp 31,044,000: Rp. 10,678,000.